2010
DOI: 10.1111/j.1478-3231.2010.02344.x
|View full text |Cite
|
Sign up to set email alerts
|

HBcrAg is a predictor of post-treatment recurrence of hepatocellular carcinoma during antiviral therapy

Abstract: HBcrAg is a predictor of the post-treatment recurrence of HCC during antiviral therapy. Serum HBcrAg and intrahepatic cccDNA suppression by NAs may be important to prevent HCC recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 37 publications
3
72
1
Order By: Relevance
“…Furthermore, serum HBcrAg levels were correlated with CCC DNA levels and frequency of HBcAg (+) hepatocytes in the liver and with liver disease activity [87,89,92,93]. It was also found to predict liver cancer development and recurrence in HBV-infected patients, and was an even better predictor than serum HBV DNA [92,94]. Serum HBcrAg was also found to associate with reactivation of occult hepatitis B following immunosuppressive therapy [91].…”
Section: Potential Applications Of Hbv Particles In Clinical Managmentioning
confidence: 99%
“…Furthermore, serum HBcrAg levels were correlated with CCC DNA levels and frequency of HBcAg (+) hepatocytes in the liver and with liver disease activity [87,89,92,93]. It was also found to predict liver cancer development and recurrence in HBV-infected patients, and was an even better predictor than serum HBV DNA [92,94]. Serum HBcrAg was also found to associate with reactivation of occult hepatitis B following immunosuppressive therapy [91].…”
Section: Potential Applications Of Hbv Particles In Clinical Managmentioning
confidence: 99%
“…Some patients also treated with tenofovir disoproxil fumarate (TDF) which shows incomplete or low responce to ADV therapy [164]. A positive correlation was found between cccDNA and HBcrAg at the incidence of HCC reoccurance, thus cccDNA is a positive haalmark of HBV related HCC reoccurance [165]. It was reported in ScienceDaily that IFN α can cause silencing of cccDNA as well as Lymphtoxin beta receptor (LTbR) agonisation and also can provide novel alternative therapeutic approach for curing CHB infection [166].…”
Section: Role Of Cccdna In Hbv-related Hcc Recurrencementioning
confidence: 99%
“…However, antiviral therapy was not an independent risk factor [22] . Some studies have demonstrated the suppressive effects of NAs on HCC recurrence [13,21] , whereas other studies did not have indicated that antiviral therapy provided favorable effects [19,20] . The differences between studies may be related to the prevalence of advanced HCC in the subjects and differences in the kinds of NAs administered.…”
Section: Hbv-related Hccmentioning
confidence: 99%
“…Since we reported that lamivudine may potentially prevent HCC recurrence after curative resection of HBV-related HCC [18] , several reports have shown the effects of NAs after treatment of HCC [13,[19][20][21] . Recently, we have evaluated the effects of NAs, primarily of entecavir, on long-term outcomes after curative resection for HCC in patients with a high serum concentration of HBV DNA ( 6 4 log 10 copies/ml) and without portal vein thrombus of the main portal vein as such portal vein thrombus is a strong risk factor for HCC recurrence and may obscure the effects of antiviral therapy [22] .…”
Section: Hbv-related Hccmentioning
confidence: 99%